PENGARUH DISIPLIN DAN FASILITAS SEKOLAH TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMA N 10 SIJUNJUNG - Hidayat, Rahmat; Ahmad, Ridwan; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This study aimed to determine the effect of discipline and school facilities to the learning   result of  geography class XI IPS SMA N 10 Sijunjung views of: 1) the discipline of learning and 2) school facilities.The study was descriptive correlational. The population in this study were students of class XI IPS in high school 10 Sijunjung listed on the Academic Year 2013/2014, amounting to 62 students. Samples were taken with a total sampling technique with a sample of 62 students.The research found that: 1) there are significant discipline of learning on learning  result of  geography  students  high school N 10 Sijunjung for t > t table (2.977  >  1.670),  low  relationship  (r  =  0.359)  and  a  very  small  contribution (12,9%), (2) the effect of school facilities on student  learning  result of  geography class XI IPS SMA N 10 Sijunjung for t > t table (2,963 > 1.670), low  relationship (r = 0,357)  and  a  very  small  contribution  (12,8 %)  and  (3)  there  are  significant learning discipline and school facilities together on learning  result of  geography class XI IPS SMA N 10 Sijunjung because Fhitung > F table ( 7.435 > 2.773 )  , the strength of the relationship between the two variables with moderate learning results ( r = 0.449 ) and the contribution including small ( 20.1 % )